PERBEDAAN INTERAKSI SOSIAL ANTARA PESERTA DIDIK YANG MENGIKUTI DAN TIDAK MENGIKUTI KEGIATAN ORGANISASI SISWA INTRA SEKOLAH (OSIS) (Studi terhadap Peserta Didik di SMA N 1 Tarusan) - MERCELINA, RIMADED - (Bimbingan dan Konseling, 2014)
The background of this research using educative participant keeping not active in osis there are fromth havenât social interaction, while the active student in their organization have better social interactionin the school, the purpose of this research is to describe; 1) the social interaction of student who hasfollowed a organization 2) the student social interaction who hasnât follow a organization 3) thedifferences social interaction of student who has followed is hasnât follow a organization. The type ofthis research atended quantitative research . and population in this research is students grade X and XI inSMA N 1 tarusan who has followed and who hasnât follow social interaction OSIS,samples of thisresearch are students who has followed a organization amounting to 75 people and who hasnât followamounting to 75 people. This research used to pull of sampel by purposive sampling. source of data inthis research are primary data and data of scunder used a instrument, while technique analyse data usedpercentage formula. The result of this research indicating that 1) social interaction between student whohas followed organization in verygood category, 2) the social interaction of student who hasnât followorganization in good category 3) there are significant differences between student social interaction whohas followed organization with hasnât follow organization.